Generation and dissipation of corrosion gas in a deep horizontal borehole repository for radioactive waste - Finsterle, Stefan; Waples, Matthew; Yang, Mengzhu; Travis, Karl P. (Frontiers in Nuclear Engineering, 2025)
The performance of a deep borehole repository for the disposal of radioactive waste may be affected by the generation of hydrogen gas produced by the corrosion of the steel canisters and the borehole casing. In particular, the evolution of a free gas phase may lead to high overpressures within the borehole and near field of the repository, displacing radionuclides dissolved in pore water, and facilitating the transport of volatile radionuclides. These processes are analyzed by numerical modeling of non-isothermal, multiphase flow and transport of hydrogen gas and water in a generic deep horizontal borehole repository completed in an argillaceous host rock. The near-field submodel addresses gas generation within and outside the canister and the effect of canister breach on near-field pressure and saturation distributions; a repository-scale model examines the effect of gas generation in a long disposal section. The models support canister and design decisions for deep borehole repositories. The simulations reveal the significance of the repository design on gas flow, both on the local scale of the components of the engineered barrier system, and on the larger scale of the repository layout. It can be concluded that for a typical design of a deep horizontal borehole repository, corrosion gases are contained within the disposal section of the borehole, or effectively dissipate into the repository’s near field without generating excessive overpressures that affect the integrity of the engineered barrier system or the overall performance of the repository.